The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ijwd.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of change: Resilience traits in Women’s Dermatological Society Forum participants by generation

Abstract: Background Physician burnout is a common problem that can have negative ramifications for both physicians and patients. Lack of effective coping mechanisms decreases resilience, which can lead to burnout, and women may be particularly vulnerable. Objective We aimed to evaluate resilience by generation among professionals in dermatology. We hope to gain a better understanding of the plasticity of resilience traits to identify modifiable resilience components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…We found that Generation Z participants demonstrated lower resilience in comparison with Generation X participants. This finding is consistent with past findings indicating that young people are less resilient than older people (Cohen et al, 2016 ; Ludwig et al, 2020 ; Gooding et al, 2012 ). However, a review of the literature indicates that resilience is domain dependent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that Generation Z participants demonstrated lower resilience in comparison with Generation X participants. This finding is consistent with past findings indicating that young people are less resilient than older people (Cohen et al, 2016 ; Ludwig et al, 2020 ; Gooding et al, 2012 ). However, a review of the literature indicates that resilience is domain dependent.…”
Section: Discussionsupporting
confidence: 93%
“…Studies of Gen Z have shown that, compared with previous generations, even prior to the COVID-19 pandemic Gen Zs exhibited higher rates of depression and anxiety, and a need for emotional support (Schroth, 2019 ). Past studies show that younger generations are less resilient than older generations (Ludwig et al, 2020 ; Gooding et al, 2012 (. However, it is not known why older people are shown to be more resilient in times of crisis.…”
mentioning
confidence: 99%
“…There are prevalent beliefs about the existence of generation differences in work engagement in the workplace. Although research has shown that differences between work engagement and meaningful work amongst generational cohorts exist, results are still inconclusive as much research conducted was focused on the retiring cohort of Baby Boomers and Generation X [ 10 ]. Hence, further evidence is required to identify generational differences in work values, engagement, and satisfaction among the present nursing workforce.…”
Section: Background and Introductionmentioning
confidence: 99%
“…The present nursing workforce comprises four generational cohorts that possesses unique values and traits. The nursing professional at a generational crossroad is experiencing an increasing share of nursing workforce predominated by Generation Y/Millennials born between the years 1994 and 1980, and Generation Z born between years 1995 to 2015 [8,9]. Existing generations of the nurses include Baby Boomers born between the years 1944 to 1964, and Generation X, born between 1965 to 1979.…”
Section: Background and Introductionmentioning
confidence: 99%